Effects of coarse sand dosage on the physic-mechanical behavior of sand concrete (Fracture and Structural Integrity, 2021)
The development and research of a new formulation of concrete integrating natural resources such as sands (from dunes and/or quarries) as well as waste from steel factories in the form of granulated slag from blast furnaces lead to the development of new sand concretes for which the improvement of specific properties will lead to a search for an agreement between production cost and performance. The objective of this research is to study the influence of the dosage of the size of the largest aggregate on the workability of sand concretes as well as on the compressive strength at 7 days, 14 days and 28 days. Five types of concrete are made by substituting aggregates (dune sand and quarry sand) with each other and with different percentages (100%, 75%, 50%, 25% and 0%). The results show that the workability of fresh concrete is considerably influenced by the nature of the sand; the richer the sand in coarse elements, the fineness modulus increases and the more handling improves. In the hardened state, the results show that optimization of the compressive strength is achieved when a good homogeneity of the concrete is achieved and when a large percentage of coarse sand is mixed with a small percentage of fine sand.
Keywords: sand concrete; extended granular; workability; mechanical behavior